Obligasi Syari’ah : Antara Teori dan Implikasi - Noor Iffatin Nadhifah; Siti Imaniatul Muflihatin (Lembaga Pengembangan Kinerja Dosen, 2024)
Sukuk has become an alternative investment for investors seeking to invest in securities. Similar to conventional bonds or debt securities, sukuk is traded in the capital market, known as the Sharia Capital Market. The Sharia Capital Market is regulated by the Capital Market Law (UUPM), with the additional requirement that all activities must align with Islamic law (syariah). Sukuk differs from conventional bonds primarily in the prohibition of fixed interest rates as returns for investors, as interest (riba) is forbidden in Islamic law. Instead, sukuk operates on principles such as profit-sharing (mudharabah) or partnership (musyarakah), ensuring that investments are conducted in businesses compliant with Islamic principles. This paper also discusses the Fatwa from the Dewan Syariah Nasional (DSN-MUI) regarding sukuk, highlighting the guidelines and terms that must be followed, including the requirement for compliance with syariah law in the type of business and the nature of returns. The paper also mentions the settlement of disputes, emphasizing the use of Sharia Arbitration to resolve any conflicts arising from sukuk contracts.